DEM classifications: opportunities and potential of its applications - Atriyon Julzarika; D Djurdjani (Brawijaya University, 2019)
DEM is a digital model that provides topographic information. DEM can be made from terrestrial surveys, aerial photography, video, optical, and radar satellites, LIDAR and multidata combination. In general, DEM can be in the form of DSM and DTM. This study aims to explain the classification of DEM based on terrestrial and non-terrestrial, the methods of DEM extraction, vertical accuracy, data formats, and technological trends. The methods of DEM extraction discussed include stereo, interferometry, DEM combination, videogrammetry, and terrestrial data interpolation. In addition, a comparison of vertical accuracy is also carried out with several methods of its extraction. DEM can be used for various applications involving land surface, especially for 3D modeling, spatial planning, geology, topography, and so on. This DEM is used to support the activities of inland waters on Rote islands.